RESISTANT LEVEL OF SOYBEAN GERMPLASM AGAINST POD SUCKING BUGS (Riptortus spp.) - Lina Herlina; Bonjok Istiaji; Dodin Koswanudin; Sutoro Sutoro (Indonesian Journal of Agricultural Science, 2021)
Increasing productivity of soybean has often been constrained by pod sucking bugs (Riptortus spp.) which caused a serious damage  and yield losses up to 80%. Breeding for obtaining soybean variety resistant to pod suckers needs the availability of soybean germplasm resistant to the pest. The study aimed to obtain a candidate for soybean variety resistant to Riptortus spp. through the selection of 100 accessions of soybean. The study included the preparation of test plants and test insects, pest infestations, observations, and looking for a practical screening method for pod sucking pests. The experiment used a completely randomized design for two treatments (infested and non-infested Riptortus spp.). Cikuray variety and PI-092734 accession were used as a control. Results showed that there was a very low correlation among variables observed. Twelve soybean accessions showed a resistance to Riptortus spp., i.e. C7301-113AC-POP, Lokal Madiun-3549, Lokal Klungkung, ML.2974, Singgalang, Lokal Jepara, Lokal Jatim, Lokal Trenggalek, Lokal Tulungagung, Lokal Tabanan, Lokal Blitar, and Lokal Kuningan 10. These accessions were more resistant than the popular released variety such as Wilis, Grobogan, Detam 2, and Gepak Ijo. Small seed size was not a major determinant of soybean resistance to pod suckers. The addition of observational components, i.e. probing preference and oviposition, indicated that crop damage was indirectly influenced by the high frequency of probing and oviposition, although its relation to plant tolerant mechanisms still needs further investigation. Indeterminate plant types require further validation as to whether they contribute significantly to plant resistance against pod sucking insects.